EVALUASI KINERJA REKSADANA SAHAM PERIODE PENELITIAN TAHUN 2009 - 2012 DENGAN MENGGUNAKAN METODE SHARPE, TREYNOR DAN JANSEN ALPHA - , Lucia Wahyuningrum ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Investment is a term that is always in connection with financial, economic, and how to manage both. However, in doing investment, other than the expected profit there is also risk. One of the investment instruments is equity - mutual fund. An investor has to posses certain planning towards the profit which will be obtained, when he is doing investment in equity-mutual fund. Hence, other than potential and most-advantageous profit from equity-mutual fund, investor also has to be warned of its associated risk. In need of information regarding equityâmutual fund performance and its potential risk, research is conducted on the performance of equityâmutual fund, by calculating and evaluating its performance using three methods, those are: Sharpe, Treynor and Jensen, which then is compared by four benchmarks: IHSG (Indeks Harga Saham Gabungan/Jakarta Composite Index), Index LQ45, Index BIS27 and Index Kompas 100. This is conducted as a means to calculate performance of risk-based equitymutual fund investment. It is also conducted in this research, a testing towards mutual fundâs performance rank consistency, along with Kendall Wâs method. It is concluded in this research that calculation using Sharpe, Treynor and Jensenâs methods which are compared with four benchmarks shows that the performances of 48 equity-mutual fund generally is poor or underperformed. Nonetheless, in this research it appears that one equity-mutual fund is always outperformed in all calculation methods and benchmarks. From the facet of performance rank consistency, it could be concluded that there is a consistency in the performance rank between three calculation methods. This could also indicate that the fund manager has conducted proper portfolio diversification.